Enhancing connectivity and trade between Central Asia regional economic cooperation countries and the world: Benefits, risks and policy implication - Yelena Kalyuzhnova; Hans Holzhacker (Asian Development Bank Institute (ADBI), 2021)
Transportation corridors and reduced trade costs are essential to develop Central Asia Regional Economic Cooperation (CAREC) countries' foreign trade. However, to intensify intra-CAREC trade as well as the region's global exports, the product portfolio of CAREC countries' industry and agriculture has to be broadened. Otherwise CAREC countries will just face strong import competition or become pure transit territories. The need and opportunities of change brought about by global decarbonization efforts and green transition, widely discussed now in connection with efforts to revive the global economy after the slump caused by the COVID-19 pandemic, make this even more urgent, especially for hydro-carbon exporters. At the same time, the green transition and the general move to more science-intense production provides opportunities for new products and employment. Broadening and expansion of the export range of products and services require a robust set of measures in areas such as trade policy, coordination of sectoral policies, diversification, and business reforms. In particular, the countries that are in the center of the CAREC region's trade flows such as Uzbekistan and Kazakhstan should step up their initiatives for industrial change and closer cooperation among the CAREC countries. The paper analyses the importance of such initiatives by CAREC countries and discusses the need for further steps in developing production that is based on countries' natural or historically accumulated comparative advantages. The paper suggests that initiatives can be clustered into economic corridors that provide economies of scale and scope and good connectivity, and therefore the impact can be scaled up. However, corridor development must be well-aligned with the overall economic policies and development plans of the countries involved. The paper concludes that progress will require redesigning schemes both for local and foreign investments, along with the development of capital markets. Trade facilitation remains an overarching objective. Better coordination of sectoral policies and priorities by measures for collaborative policy formulation and implementation, alignment of national and regional planning, and regulatory convergence in the region is required. Recommendations include suggestions to revise development plans in the light of accelerated technological change, not least due to COVID-19, and to facilitate the social change brought about by the technological change by active requalification and labor market policies.
Keywords: F13; P25; P28; O19; Q35; 330; transportation corridors; trade; CAREC countries; COVID-19; connectivity